Science Outreach at the BTC Institute - Aerospace Outreach Program & Special Initiatives Program - Bielec, Barbara (Proceedings of the Wisconsin Space Conference, 2015)
The BioPharmaceutical Technology Center Institute (BTC Institute) is a non-profit educational organization founded in 1993; located in Fitchburg, WI. During the summers of 2013 and 2014, the BTC Institute offered teacher training in biotechnology through two graduate education courses, Biotechnology: The Basics (2013 & 2014) and Biotechnology: Beyond the Basics (2013). Teachers of a wide variety of subjects with varied levels of teaching experience were active participants in this lab-based learning that provided teachers with training, background and curriculum materials including information about NASA and biotechnology. In addition to the teacher courses, the BTC Institute in partnership with the African American Ethnic Academy, Inc. (AAEA), a Madison non- profit organization, also offered "A Celebration of Life!, a science program for upper elementary and middle school students. The focus of the 2013 program was Energy and the focus of the 2014 program was Flight.